A Model of Auditory-Cognitive Processing and Relevance to Clinical Applicability. (July 2016) - Edwards, Brent
Abstract : Hearing loss and cognitive function interact in both a bottom-up and top-down relationship. Listening effort is tied to these interactions, and models have been developed to explain their relationship. The Ease of Language Understanding model in particular has gained considerable attention in its explanation of the effect of signal distortion on speech understanding. Signal distortion can also affect auditory scene analysis ability, however, resulting in a distorted auditory scene that can affect cognitive function, listening effort, and the allocation of cognitive resources. These effects are explained through an addition to the Ease of Language Understanding model. This model can be generalized to apply to all sounds, not only speech, representing the increased effort required for auditory environmental awareness and other nonspeech auditory tasks. While the authors have measures of speech understanding and cognitive load to quantify these interactions, they are lacking measures of the effect of hearing aid technology on auditory scene analysis ability and how effort and attention varies with the quality of an auditory scene. Additionally, the clinical relevance of hearing aid technology on cognitive function and the application of cognitive measures in hearing aid fittings will be limited until effectiveness is demonstrated in real-world situations.